TRANSFORMATIONS IN THE BANKING BUSINESS MODEL IN IRAQ UNDER THE NEW REGULATORY RESTRICTIONS FOR THE PERIOD (2021-2024) - Ahmed Abbas Fadhil (Scholars Digest Publishing, 2026)
The aim of this study is to examine the changes in the banking business model in Iraq for years (2021- 2024) due to recent regulatory restrictions introduced by CBI, regarding governance, liquidity, compliance and service regulation. The research was based on both theoretical and empirical aspects by studying three Iraqi banks (National Iraqi Bank, Baghdad Bank and Al-Rafidain Bank) through the indicators of financial, operative and structural. “Private-sector banks have done a better job simply because they are more diversified in their revenue base, had been aggressive in rolling out digital services and were much more focused on operational efficiency as the way to become profitable, whereas public-sector banks still played by the traditional rules,” said Dan Fineman, co-author of the study. Furthermore, the findings indicated that there are distinct differences in the transformation routes and a near complete absence of overall strategic vision within the Iraqi banking sector which points to an urgent requirement to re-engineer existing operational models and tie them more closely to recent technical as well as compliance developments.
Keywords: Banking Business Model Transformation, Regulatory Restrictions, Iraqi Banking Sector.